Operational Rations Current and Future of the Department of Defense - Meyer, A I; Klicka, M V (1982)
The operational rations that are now available to meet United States Military Service needs and those presently under development are categorized as: General Operational Rations, Special Operational Subsistence, Survival Subsistence, and Furture Feeding Concepts. Each ration is briefly described and where applicable typical menus are included. A historical summary outlines past rations in terms of their functions, contributions, and relationships to present and future rations.